Associations of accelerometer-measured sedentary behavior and gray matter volume in healthy young adults - Giurgiu, Marco; Benedyk, Anastasia; Reichert, Markus; Berhe, Oksana; Braun, Urs; Ebner-Priemer, Ulrich; Tost, Heike; Meyer-Lindenberg, Andreas (European journal of sport science, 2025)
Sedentary lifestyles can be seen as one of the central risk factors for poor health in the 21st century. Previous studies indicated negative associations between sedentary behavior and brain health. However, the neurological link between sedentary behavior and gray matter volume remains unclear. This study aimed to assess the relationship between device-based measured sedentary time and gray matter volume in healthy young adults. A total of 181 participants wore a move-II hip-accelerometer to measure sedentary time and physical activity over seven consecutive days. Following the study week, participants underwent a structural magnetic resonance imaging (MRI) scan to assess gray matter volume. Whole-brain voxel-based morphometry analysis was conducted on the MRI data, and group comparisons focused on a region of interest to examine the potential association of moderate-to-vigorous intensity physical activity (MVPA). On a daily average, participants spent 6.04 h (SD = 2.2) in sedentary and 1.2 h (SD = 0.51) in MVPA. More sedentary time was associated with lower gray matter volume in the left superior frontal gyrus (pFWE = 0.007). Furthermore, participants with high levels of MVPA demonstrated higher gray matter volume in the left (pFWE = 0.028) and right (pFWE = 0.022) superior frontal gyrus compared to the sedentary group with low MVPA engagement. Sedentary behavior may be linked to smaller gray matter volume in brain structure, particularly in the superior frontal gyrus, which plays an important role in motor and cognitive brain networks. Intriguingly, people with high sedentary behavior but concurrently high levels of MVPA did not exhibit this negative gray matter association.